Copper alloy pipe and preparation method and application thereof

By adding Zr, B, and Mn to Cu-Sn-P alloys and controlling their content and proportion, combined with specific heat treatment and stretching processes, uniformly distributed MnZr and BMn compounds are formed, solving the problem of insufficient comprehensive performance of copper alloy tubes in refrigeration and air conditioning. This achieves high strength, good electrical and thermal conductivity, and corrosion resistance, while improving processing performance and stability.

CN119265448APending Publication Date: 2025-01-07NINGBO JINTIAN COPPER TUBE

Patent Information

Application Number
CN202411300735.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing copper alloy pipes used in refrigeration and air conditioning systems suffer from problems such as surface scratches, flared end deformation, difficulty in bending, easy cracking after expansion, local softening after 800℃ brazing, and corrosion perforation under atmospheric conditions. These issues lead to refrigerant leakage in the connecting pipes, and their overall performance fails to meet processing and usage requirements.

Method used

By adding Zr, B, and Mn to Cu-Sn-P alloys, controlling their content and ratio, and regulating the quantity and grain size of MnZr and BMn compounds, combined with specific heat treatment and stretching processes, uniformly distributed MnZr and BMn compounds are formed, improving the strength, electrical conductivity, thermal conductivity, and corrosion resistance of copper alloy tubes, and enhancing their bending, flaring, welding, and pressure resistance properties.

Benefits of technology

It achieves high strength, good elongation, excellent electrical and thermal conductivity, and corrosion resistance in copper alloy tubes, improves processing performance such as bending, flaring, welding, and pressure resistance, reduces the risk of cracking during processing, and meets the high pressure and high temperature stability requirements of refrigeration and air conditioning systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005047582880000131
    Figure BDA0005047582880000131
  • Figure BDA0005047582880000141
    Figure BDA0005047582880000141
  • Figure BDA0005047582880000151
    Figure BDA0005047582880000151
Patent Text Reader

Abstract

The invention discloses a copper alloy pipe and a preparation method and application thereof, and the copper alloy pipe comprises the following components in percentage by mass: 0.01%-0.80% of Sn, 0.005%-0.05% of P, 0.01%-0.10% of Zr, 0.001%-0.01% of B, 0.001%-0.01% of Mn and the balance of Cu and inevitable impurities. Wherein the copper alloy pipe contains MnZr and BMn compound particles, the number of the MnZr compound particles on the cross section of the copper alloy pipe is 0.005-0.15 / mu m < 2 >, and the number of the BMn compound particles on the cross section of the copper alloy pipe is 0.005-0.2 / mu m < 2 >. By adding Zr, B and Mn and controlling the content of Zr, B and Mn, the preparation process and the like, the number and uniformity of MnZr and MnB compounds are regulated and controlled, and the tensile strength, ductility, corrosion resistance, bending, flaring, welding, pressure resistance and other machining performance of the copper alloy pipe are improved; and the prepared copper alloy pipe fully meets the application requirements of heat conduction pipes of air conditioner heat exchangers, air conditioner indoor and outdoor unit connecting piping and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloys, and in particular relates to a copper alloy tube and a preparation method and application thereof. Background Art

[0002] With the development of new CO2 refrigerants for air conditioners, copper alloy tubes for refrigeration and air conditioning, including heat exchanger tubes and indoor and outdoor connecting pipes, have put forward higher requirements for the high pressure resistance of materials. In response to this requirement, a solution has been proposed to replace phosphorus deoxidized copper with Co-P or Sn-P copper alloy tubes with higher strength than phosphorus deoxidized copper, which can fully meet the high strength and high pressure resistance requirements under thin wall conditions required by new CO2 refrigerants.

[0003] However, for copper tubes used in refrigeration and air conditioning, traditional TP2 is prone to surface scratches and bell mouth deformation during the connection process. High-strength Co-P or Sn-P alloy tubes also expose problems such as difficult bending, easy cracking of the bell mouth after tube expansion, local softening after 800℃ brazing, and long-term corrosion and perforation in the atmosphere. In severe cases, it may cause refrigerant leakage accidents in the connecting pipes. In this way, even if the heat exchanger works well, it is difficult for the entire air conditioning system to work normally and effectively.

[0004] As copper pipes for refrigeration and air conditioning, the pipe material's own characteristics and processing characteristics directly affect the overall performance of the air conditioner. Not only are the pipes required to have good tensile strength, elongation, electrical conductivity, thermal conductivity and corrosion resistance, but they must also have excellent processing and application characteristics such as bending, flaring, welding, pressure resistance and sealing.

[0005] Patent document CN101469961A discloses a copper alloy tube for heat exchangers with excellent fracture strength, which has a composition containing a specific amount of Sn and P, an average grain diameter of 30 μm or less, and a high tensile strength of 250 MPa or more in the longitudinal direction of the tube, wherein the copper alloy tube has a collective structure with an orientation distribution density of Goss orientation of 4% or less, thereby improving the fracture strength. The copper alloy tube is durable and has excellent fracture strength even if it is thin-walled under the high operating pressure of new refrigerants such as carbon dioxide and HFC-based Freon.

[0006] Patent document CN102051500 discloses a copper alloy tube for air conditioning and refrigeration, the copper alloy tube contains Mn: 0.1-1.5wt%, P: 0.015-0.04wt%, mixed rare earth metal: 0.001-0.1wt%, the balance is Cu and inevitable impurities, and the average grain size is 0.005-0.030mm. The copper alloy of the invention is measured by corrosion electrochemistry, and its current density is more than 10% less than the current density of TP2. The copper alloy tube can form a dense and uniform passivation film on the surface of the copper alloy tube in a carboxylic acid or carboxyl acid atmosphere to hinder the diffusion of carboxyl groups in copper, and can meet the requirements of copper tubes for air conditioning and refrigeration.

[0007] Although the prior art has studied copper alloy tubes for air conditioners, the prior art usually only improves one aspect of the performance of the copper alloy tube, resulting in its comprehensive performance failing to meet the processing and application requirements of the copper alloy tube for air conditioners, making the copper alloy tube prone to cracking, poor thermal stability, easy corrosion, and other problems during processing and use. Therefore, it is necessary to provide a copper alloy tube and a preparation method thereof to improve the installation and use of copper tubes for refrigeration and air conditioning. Summary of the invention

[0008] The object of the present invention is to provide a copper alloy tube and its preparation method and application. The copper alloy tube of the present invention has good tensile strength, elongation, electrical conductivity, thermal conductivity and corrosion resistance, and has excellent processing characteristics such as bending, flaring, welding and pressure resistance, and its preparation method is simple, and can be used to prepare heat conduction pipes of air conditioner heat exchangers, connecting pipes for indoor and outdoor units of air conditioners, etc.

[0009] The first aspect of the present invention provides a copper alloy tube, comprising the following components in percentage by mass: Sn: 0.01-0.80%, P: 0.005-0.05%, Zr: 0.01-0.10%, B: 0.001-0.01%, Mn: 0.001-0.01%, and the balance is Cu and unavoidable impurities; wherein the copper alloy tube contains MnZr and BMn compound particles, and the number of MnZr compound particles on the cross section of the copper alloy tube is 0.005-0.15 / μm 2 The number of BMn compound particles is 0.005 to 0.2 per μm. 2 .

[0010] The present invention adds Zr, B and Mn on the basis of the Cu-Sn-P alloy composition, and controls their contents and proportions. By regulating the amount of MnZr and BMn compounds in the alloy and the size and uniformity of the microstructure grains, the strength, elongation, electrical conductivity, thermal conductivity and corrosion resistance of the copper alloy tube are improved, and the processing properties such as bending, flaring, welding and pressure resistance are improved.

[0011] The addition of Sn element can significantly improve the tensile strength and yield strength of copper tubes, while inhibiting the coarsening of grains. As a solute atom, Sn is different in size from the matrix copper atom. The strain field caused by the distortion of the local crystal lattice will produce changes in the interaction with the dislocation, which will eventually increase the deformation resistance of the crystal and produce the effect of solid solution strengthening; at the same time, it can improve the tensile strength and yield strength of the copper tube, so as to meet the high pressure resistance requirements under the conditions of the same outer diameter and wall thickness of the copper tube. In addition, the addition of Sn element has the effect of improving the heat resistance of the material, which is beneficial to brazing processing.

[0012] However, if the Sn content is too high, it will be detrimental to electrical conductivity, thermal conductivity and elongation plasticity, and wrinkles or cracks will easily occur in the bending part. When the Sn content is less than 0.01%, the solid solution strengthening effect of Sn is not obvious, and the tensile strength and yield strength cannot be significantly improved; when the Sn content is greater than 0.8%, not only the electrical conductivity, thermal conductivity and elongation plasticity are lost, which is not conducive to the refrigeration and processing of copper tubes, but the high Sn content is also prone to segregation, obtaining uneven cast structure, resulting in obvious anisotropy of the mechanical properties of the copper tube, greatly reducing the uniformity of hardness and strength. Therefore, the Sn content in the present invention is 0.01-0.80%.

[0013] The P element can deoxidize and improve the fluidity of the melt. At the same time, P can also increase the strength of the copper tube, inhibit grain growth, and improve the welding performance of the material. However, when the P content increases, grain boundary segregation is likely to occur, which seriously reduces the plasticity of the material, is not conducive to the bending of the copper tube, is prone to cracks, and the sensitivity of stress corrosion cracking will also increase.

[0014] When the P content is lower than 0.005%, the improvement effect of P on the copper tube is not obvious; when the P content is greater than 0.05%, the elongation plasticity is significantly lost. Therefore, the P content in the present invention is controlled to be 0.005-0.05%.

[0015] The addition of Zr element is dissolved into the copper matrix through solid solution treatment to form a supersaturated solid solution, and then the solid solution is decomposed into dispersed precipitate phases during heat treatment, thereby improving the strength of the alloy. At the same time, the more important role of Zr addition is that it can greatly reduce the grain boundary energy, produce solute drag and second phase pinning grain boundaries, increase the recrystallization temperature and heat resistance of the alloy, so that the alloy obtains high strength and high softening point. In addition, the solubility of Zr in the Cu matrix is ​​very low, and the low-solubility alloying element Zr has a very limited effect on the overall electrical and thermal conductivity of the alloy, which can ensure the good heat exchange effect of the alloy.

[0016] If the Zr content is less than 0.01%, the strength is insufficient and the effect on increasing the recrystallization temperature is not great; when the Zr content exceeds 0.1%, although the strength of the alloy is improved, the size of the precipitated phase increases and enrichment occurs, and the conductivity and plasticity decrease significantly. In order to obtain the best balance of strength, heat resistance, plasticity, and electrical and thermal conductivity, the Zr content is controlled at 0.01-0.10%.

[0017] B plays the role of deoxidation and grain refinement, and forms nano-scale boron metal compounds, which are finely and dispersedly distributed at the grain boundaries, strengthening the grain boundaries, thereby inhibiting the cracking of the alloy caused by the diffusion of oxygen from the alloy surface through the grain boundaries to the interior, and can also promote the formation of dynamic recrystallization, thereby increasing the hardness and softening point of the alloy.

[0018] Adding more than 0.001% boron to the alloy of the present invention can improve the strength, hardness, corrosion resistance and softening point of the alloy, and has almost no effect on the electrical conductivity; but when the boron content exceeds 0.01%, the electrical conductivity, thermal conductivity and plasticity of the alloy are reduced. Therefore, the present invention controls the addition amount of B to 0.001-0.01%.

[0019] Mn can be infinitely dissolved in copper alloys, and plays a role in solid solution strengthening by being dissolved in large quantities in the copper matrix. The Mn element improves the strength and hardness of the copper alloy. At the same time, the large amount of lattice distortion caused by the solid solution will also enhance the scattering of electrons, greatly reducing the electrical and thermal conductivity of the copper alloy. Therefore, existing high-conductivity copper alloys often do not contain manganese.

[0020] The Mn content of the alloy of the present invention is preferably 0.001-0.01%. When the Mn content is lower than 0.001%, the strengthening effect is not obvious and the softening temperature cannot be increased. When the Mn content is higher than 0.01%, the MnZr and BMn intermetallic compounds agglomerate, which affects the overall performance of the material and has a greater impact on the electrical and thermal conductivity. Therefore, in the present invention, the Mn content is controlled to be 0.001-0.01%.

[0021] The present invention can make Mn and Zr, Mn and B produce strong interactions by adding an appropriate amount of Mn, produce high melting point MnZr, BMn hard metal compound precipitation phase, evenly distributed in the copper matrix, play a role of dispersion strengthening, thereby ensuring the mechanical properties of the alloy. At the same time, because the softening point of the metal phase is greater than 800°C, it can also improve the overall softening temperature of the alloy, improve the thermal stability of the alloy, and improve the local softening problem after 800°C brazing.

[0022] However, if the distribution of the precipitated phases of MnZr and BMn intermetallic compounds is uneven, it will have a great impact on the performance of the alloy, and it will easily lead to deformation and cracking during the later processing of bending and expanding pipes, affecting the normal use of the material. At the same time, it will also affect the electrical and thermal conductivity of the alloy, which is not conducive to the heat exchange energy efficiency of the pipe. Therefore, the uniform distribution of MnZr and BMn intermetallic compounds is of great significance for improving the comprehensive performance of the material. The preparation method of the present invention can achieve uniform dispersion of MnZr and BMn intermetallic compounds in the alloy by controlling the heat treatment and processing technology.

[0023] Preferably, in the copper alloy tube, the mass ratio of Zr to Mn elements satisfies: 0.1≤Mn / Zr≤1, and the mass ratio of B to Mn elements satisfies: 0.1≤Mn / B≤8.

[0024] The thermal stability of the alloy of the present invention is greatly affected by the content of the three elements Zr, B and Mn. As the alloy processing rate increases, the dislocation stacking density of the alloy gradually increases, and the stability at high temperature also deteriorates accordingly. In the case of alloy dislocation density stacking, trace amounts of Zr and B are distributed on the grain boundaries of the copper matrix, which can alleviate the excessive concentration of dislocation density of the matrix during processing and deformation, but excessive Zr and B are prone to segregation in the matrix.

[0025] A certain content of Mn can promote the formation of high-melting-point hard MnZr and BMn compounds, and prevent excessive Zr and B from accumulating in the copper matrix in the form of simple substances; when there is too much Mn, excessive solid solution of Mn will significantly reduce the electrical conductivity, thermal conductivity and processing performance of the alloy. Therefore, considering the thermal stability, electrical conductivity, thermal conductivity and processing performance of the alloy, the mass ratio of Zr, B and Mn is controlled within 0.1≤Mn / Zr≤1 and 0.1≤Mn / B≤8 in the present invention.

[0026] The present invention adds appropriate amounts of three elements, Zr, B and Mn, and utilizes the interaction of Zr, B and Mn in a high-temperature metal melt to form uniformly distributed MnZr and BMn compounds, which have high hardness. The comprehensive mechanical properties of the alloy are further improved by superposition of the work hardening of the Sn solid solution phase and the copper matrix and the dispersion strengthening effect of the hard MnZr and BMn compounds. On the other hand, since the B-Mn compound is a high-melting-point compound with a melting point exceeding 1800°C, it is uniformly distributed in the alloy matrix and can effectively improve the thermal stability of the alloy.

[0027] Preferably, the copper alloy tube has an average grain diameter of 15 μm or less, and a standard deviation of the average grain diameter of 1.5 μm or less.

[0028] In order to ensure the processing performance of copper alloy tubes such as bending, expanding, and flaring, it is required that the grains of the copper alloy organization be refined and the deviation of the diameters of each grain be suppressed. In the processing of bending, expanding, and flaring, not only the average grain diameter has a great influence on the bending processability, but also the deviation of the grain diameter has a great influence on the bending processability. Small and uniform organization grains can better cooperate with deformation and reduce stress concentration. At the same time, the more grain boundaries there are, the better the corrosion resistance of the copper alloy. In order to obtain a copper alloy with high strength and excellent processability, it is necessary to reduce the coarse grains in the copper alloy organization and make the diameters of each grain as fine as possible. Therefore, in the present invention, the average grain diameter of the copper alloy tube organization is controlled to be below 15μm, and the standard deviation of the average grain diameter is controlled to be below 1.5μm.

[0029] When the average grain diameter exceeds 15 μm and the standard deviation of the average grain diameter exceeds 1.5 μm, the coarse grains in the copper alloy structure increase, the deviation of each grain diameter also becomes larger, the processing performance such as bending, expanding, and flaring deteriorates, and processing cracks are prone to occur, and in severe cases, accidents such as refrigerant leakage may occur. More preferably, in the present invention, the average grain diameter of the copper alloy tube is less than 10 μm, and the standard deviation of the average grain diameter is less than 0.9 μm.

[0030] Preferably, the copper alloy tube further comprises Fe and Si, and the total mass percentage of Fe and Si is less than 0.0030%.

[0031] One of the common corrosion failures of copper alloy tubes in atmospheric environment is intergranular corrosion. Grain boundary is the misalignment area between metal grains, and it is also a high energy area with strong chemical activity. Therefore, in most cases, the grain boundary corrodes faster than the grain itself. The formation phase of Fe and Si elements easily occurs on the grain boundary, which is the key element to cause intergranular corrosion. Therefore, the present invention requires that the content of Si and Fe is less than 0.0030%, which reduces the probability of intergranular corrosion. More preferably, the content of Si and Fe is less than 0.0015%.

[0032] Preferably, the copper alloy tube of the present invention further comprises 0.001-0.01% by mass of X, wherein X is selected from at least one of Mg, Al, Cr, Ni or RE (rare earth element). Preferably, the RE comprises La, Ce and Y.

[0033] The X element can play a certain degree of strengthening effect. During the melting and casting process, the X element can act as a deoxidizer, or as a nucleation center to increase the nucleation rate of the alloy, thereby achieving the purpose of purifying the melt and refining the grains. The reduction of the oxygen content of the alloy melt will reduce the tendency of oxidized inclusions; the ingot with fine grains provides a good initial condition for processing the finished pipe, which helps to improve the mechanical properties and processing properties of the pipe of the present invention. When the content of the optional element X is less than 0.001%, the effect of purifying the melt and refining the grains is not obvious; when its content is higher than 0.01%, the excessive X element will have a greater negative impact on the electrical and thermal conductivity of the alloy. Therefore, the content of the X element is controlled at 0.001-0.01% in the present invention.

[0034] Preferably, the copper alloy tube of the present invention has a tensile strength in the longitudinal direction of ≥250 MPa, and a tensile strength in the circumferential direction of ≥235 MPa.

[0035] The rupture problem of copper tubes when the refrigerant is working is caused by cracks at a certain point. The fundamental reason is that under the refrigerant operating pressure, the pressure acting on the copper tube in the circumferential direction is greater than the pressure in the longitudinal direction, resulting in cracks. Therefore, if you want to improve the pressure resistance of copper tubes, the key is to improve the strength of the copper tube in the circumferential direction and inhibit the cracking of the heat transfer tube. When the tensile strength of the copper tube in the circumferential direction is ≥235MPa, the copper tube can withstand a simulated test of 13MPa water pressure, which meets the refrigerant operating pressure conditions. At the same time, the tube has moderate resistance to deformation and is more suitable for bending installation; when the tensile strength of the copper tube in the circumferential direction is <235MPa, there is a risk of tube pressure rupture. Therefore, the tensile strength of the copper tube in the circumferential direction of the present invention is ≥235MPa.

[0036] Preferably, the yield strength YS of the copper alloy tube in the circumferential direction of the present invention is LD Yield strength YS in the longitudinal direction TD Ratio YS LD / YS TD ≥0.95.

[0037] The deformation of copper tube bending and expansion processing directly depends on the anisotropy control of copper alloy tubes. The coordinated deformation in different directions is crucial for bending and expansion processing. For example, conventional tensile work hardening will inevitably increase the strength of the copper tube in a single longitudinal direction to a greater extent, which is not conducive to the bending and expansion processing of copper tubes and is prone to cracking. Therefore, the smaller the anisotropy of copper alloy tubes, the more conducive it is to the bending and expansion processing of copper tubes.

[0038] The anisotropy of the copper alloy tube in the present invention is mainly reflected in the difference between the yield strength in the circumferential direction of the copper tube and the yield strength in the longitudinal direction of the copper tube. Under the condition of a certain tensile strength, the yield strength in the circumferential direction of the copper tube is improved, which can enhance the bursting pressure of the tube; the yield strength in the longitudinal direction of the copper tube is improved, which can enhance the bending and expansion processing performance of the tube, making it less likely to crack when the tube is bent and expanded. Therefore, the present invention requires the yield strength YS of the copper alloy tube in the circumferential direction to be LD And the longitudinal yield strength YS TD Ratio YS LD / YS TD ≥0.95, which is conducive to ensuring better bending and expansion processability. LD / YS TD When it is less than 0.95, when the yield strength of the copper alloy tube is improved, the yield strength in the longitudinal direction increases significantly, and the elongation decreases, which is not conducive to the bending and expanding processing of the tube, and it is easy to cause orange peel or cracks.

[0039] Preferably, the copper alloy tube of the present invention has an average grain diameter of 15 μm or less and a bursting pressure of 30 MPa or more.

[0040] Preferably, the copper alloy tube of the present invention has an average grain diameter of less than 20 μm and a bursting pressure of more than 30 MPa after being heated at 800° C. for 15 seconds.

[0041] Preferably, the copper alloy tube of the present invention has an average grain diameter of less than 25 μm and a bursting pressure of more than 29 MPa after being heated at 1000° C. for 15 seconds.

[0042] Preferably, the copper alloy tube of the present invention has an average grain diameter of less than 30 μm and a bursting pressure of more than 28 MPa after being heated at 1065° C. for 15 seconds.

[0043] The second aspect of the present invention provides a method for preparing the copper alloy tube, comprising the following steps: smelting → casting → homogenization annealing → extrusion → rolling → primary stretching → primary annealing → secondary stretching → secondary annealing;

[0044] Wherein, the primary annealing temperature is 650-900°C, the annealing time is 0.1-2h, and the cooling rate after the primary annealing is greater than 30°C / s;

[0045] The elongation coefficient of the secondary stretching is 0.8 to 1.5.

[0046] The purpose of the primary annealing is to carry out a solid solution treatment on the pipe after rolling and primary stretching cold working. On the one hand, it plays an important role in the dispersion of Sn, Zr and Mn, and the dispersion of Sn, Zr and Mn can effectively control the grain size of the matrix. More importantly, the solid solution temperature can effectively control the subsequent precipitation and uniform distribution of MnZr and BMn compounds to avoid their agglomeration in the matrix. When the annealing temperature is higher than 900°C and the time exceeds 2h, the pipe is prone to overheating, resulting in severe oxidation or melting of the grain boundaries, and the risk of cracking along the grain boundaries in subsequent processing; when the annealing temperature is lower than 650°C and the time is less than 0.1h, the solid solution effect is not good, and it is difficult to achieve the subsequent precipitation and uniform distribution of MnZr and BMn compounds, which is not conducive to the comprehensive performance of the pipe such as strength, pressure resistance and thermal stability. Therefore, the primary annealing temperature in the present invention is 650-900°C, and the annealing time is 0.1-2h.

[0047] The cooling rate in the solution treatment is very important and directly affects the solution effect. When the rapid cooling rate is less than 30°C / s, the solute atoms may precipitate on the surface of the copper matrix, which is not conducive to the aging strengthening effect in the subsequent process, and it is difficult to obtain a suitable amount of MnZr and BMn compounds, which is not conducive to the improvement of the mechanical properties and thermal stability of the pipe. Therefore, in the present invention, the rapid cooling rate after the completion of the primary annealing heating is greater than 30°C / s.

[0048] The purpose of secondary stretching is to obtain the required outer diameter and wall thickness, and at the same time determine the mother tube structure and performance of the pipe product, so the secondary stretching process is very important. In order to ensure good uniform deformation of the mother tube and uniform tissue crushing, the elongation coefficient of the secondary stretching process in the present invention is controlled at 0.8-1.5. When the elongation coefficient of the secondary stretching process is less than 0.8, the recrystallized structure obtained by the first annealing will not be sufficiently crushed due to the small elongation coefficient, and it is impossible to obtain sufficient processing fiber structure, thereby affecting the good yield strength and pressure resistance of the final pipe; when the elongation coefficient of the secondary stretching process is greater than 1.5, the recrystallized structure obtained by the first annealing will have a large deformation and uneven structure, which is not conducive to the thermal stability of the bending, flaring and brazing processing of the pipe. Therefore, the elongation coefficient of the secondary stretching in the present invention is 0.8-1.5.

[0049] Preferably, the secondary stretching passes are 5 to 8 passes, the elongation coefficients of the first two passes are 1.2 to 1.5, and the elongation coefficients of the last three passes are 0.8 to 1.3.

[0050] The pass design and elongation coefficient of the secondary stretching process directly affect the texture formation of the "soft-oriented" and "hard-oriented" components of the pipe, thereby affecting the hardness, strength and thermal stability of the pipe. When the number of stretching passes is less than 5, the small number of passes determines the large processing rate stretching of a single pass. At this time, the effect of strong stretching will not only affect the tolerance of the pipe after coiling, but also increase the area proportion of the hard-oriented copper-type texture and Y-oriented texture. The texture of the hard-oriented component increases significantly, and a large amount of dislocation accumulation and strain accumulation directly affect the final pipe's organizational grain size deviation and high-temperature thermal deformation performance; when the number of stretching passes is more than 8, not only is the coiling process production efficiency low, but the surface damage points are increased, which is not conducive to the bending and expansion performance of the pipe.

[0051] In order to obtain a copper alloy tube with processing application performance in the present invention, under the premise of ensuring a multi-pass stretching process, the elongation coefficients of the first two passes are 1.2 to 1.5, and the elongation coefficients of the last three passes are 0.8 to 1.3. In the design process of the stretching process with more than 5 passes, the first two passes are called the pre-stretching stage. At this time, it is necessary to ensure that the grains are broken to the greatest extent and a large number of deformation textures are formed to provide a suitable hard-oriented component texture basis for subsequent annealing. When the elongation coefficients of the two passes in the pre-stretching stage are both less than 1.2, the processing stress is small, resulting in insufficient dislocation density, which not only fails to fully break the large and small angle grain boundaries in the recrystallized structure, but is also not conducive to the formation of deformation texture, affecting the bending and flaring processing effects of the pipe; when the elongation coefficients of the first two passes in the pre-stretching stage are both greater than 1.5, the stretching process cannot guarantee the surface quality of the pipe, and the pipe may break in severe cases. As the number of stretching passes increases, the recrystallized structure of the pipe is largely converted into a processed fiber structure, and the recrystallized texture is largely converted into a deformation texture, and the plasticity gradually decreases at this time.

[0052] The design of the elongation coefficients of the last three passes of drawing must not only control the surface quality stability of the coiled tube, but also ensure the acquisition of copper-type texture, Gaussian texture and Y-oriented texture with appropriate area distribution. When the elongation coefficients of the last three passes of coiling are all greater than 1.3, it is impossible to ensure a certain area distribution of Gaussian texture, reduce the coordinated deformation effect of the soft-oriented component texture, and affect the size of the high-temperature brazing of the copper tube; when the elongation coefficients of the last three passes of coiling are all less than 0.8, the coiling process as a whole cannot form a deformation texture with sufficient area distribution, which is not enough to support the texture conversion required by the annealing process, affecting the thermal stability of the final tube.

[0053] Preferably, the secondary annealing temperature is 400-650° C., and the annealing time is 0.5-8 h.

[0054] Secondary annealing can obtain uniform and fine structure, so that MnZr and BMn compounds are evenly distributed, and at the same time, the performance of the pipe can be adjusted to a soft state (O state). When the annealing temperature is higher than 650°C and the time exceeds 8h, not only the pipe structure is coarse and uneven, it is difficult to obtain the ideal average grain diameter and average grain diameter deviation of the structure, and MnZr and BMn compounds are prone to agglomeration, which is not conducive to the expansion and bending performance of the pipe; when the annealing temperature is lower than 400°C and the time is less than 0.5h, the pipe has residual processing structure and the performance is hard. At the same time, it is difficult to obtain the appropriate amount of MnZr and BMn compounds, which is not conducive to the thermal stability of the brazing processing of the pipe. Therefore, in the present invention, the secondary annealing temperature is controlled at 400-650°C, and the annealing time is controlled at 0.5-8h.

[0055] The third aspect of the present invention provides the use of the copper alloy tube in the preparation of heat transfer tubes of air conditioner heat exchangers, connecting pipes between indoor and outdoor units of air conditioners, pipes inside the machine or pipe assemblies. The copper alloy tube of the present invention has good tensile strength, elongation and corrosion resistance, and has excellent processing properties such as bending, flaring, welding and pressure resistance, and is particularly suitable for preparing indoor and outdoor connecting pipes for cold air conditioners.

[0056] Compared with the prior art, the present invention has at least the following beneficial effects:

[0057] (1) The present invention adds Zr, B, and Mn to the Cu-Sn-P alloy composition, and controls their contents and proportions. By regulating the amount of MnZr and BMn compounds in the alloy and the size and uniformity of the microstructure grains, the tensile strength, elongation, electrical conductivity, thermal conductivity, and corrosion resistance of the copper alloy tube are improved, and the processing properties such as bending, flaring, welding, and pressure resistance are improved.

[0058] (2) The present invention further improves the bending, flaring, welding and pressure resistance processing characteristics of the copper alloy tube by regulating the average grain diameter of the copper alloy tube structure and strictly controlling the standard deviation of the average grain diameter of the structure to less than 1.5 μm, thereby reducing the risk of cracking during the processing.

[0059] (3) In the preparation process of the copper alloy tube, the present invention realizes the dispersion of Sn, Zr and Mn by improving the stretching and annealing processes, and effectively controls the grain size of the matrix, the subsequent precipitation and uniform distribution of MnZr and BMn compounds, thereby improving the strength, pressure resistance and thermal stability of the material and its processing performance.

[0060] (4) The copper alloy tube of the present invention has a longitudinal tensile strength of ≥250 MPa, a circumferential tensile strength of ≥235 MPa, and a circumferential yield strength YS LD And the longitudinal yield strength YS TD Ratio YSLD / YS TD ≥0.95; after heating at 800℃ for 15s, the average grain diameter of the organization is less than 20μm, and the bursting pressure is more than 30MPa; after heating at 1000℃ for 15s, the average grain diameter of the organization is less than 25μm, and the bursting pressure is more than 29MPa; after heating at 1065℃ for 15s, the average grain diameter of the organization is less than 30μm, and the bursting pressure is more than 28MPa, and it has excellent corrosion resistance, electrical conductivity and thermal conductivity, etc., which fully meets the application requirements of heat pipes of air-conditioning heat exchangers, connecting pipes of air-conditioning internal and external units, and is easy to install and use. DETAILED DESCRIPTION

[0061] The present invention is further described in detail below with reference to the embodiments.

[0062] The specific compositions of the alloys of the embodiments of the present invention and the comparative examples are shown in Table 1.

[0063] The preparation process is: batching → smelting → casting → homogenization annealing → extrusion → rolling → primary stretching → primary annealing → secondary stretching → secondary annealing → cleaning. The specific preparation method is:

[0064] 1) Ingredients: Ingredients are prepared according to the ingredients in Table 1, using electrolytic pure copper plate, pure Sn, phosphor copper CuP14, and other elements are added in the form of master alloys;

[0065] 2) Melting: The melting temperature is 1150-1200℃, and the charcoal covering thickness is 180-220mm;

[0066] 3) Semi-continuous casting: casting temperature is 1150-1180°C, casting speed is 80-120mm / min, specifications

[0067] 4) Homogenization annealing: annealing temperature is 650-900°C, annealing time is 0.5-2h;

[0068] 5) Extrusion: extrusion temperature is 750~950℃, speed is 1~10m / min, extrusion specifications

[0069] 6) Rolling: total processing rate shall not exceed 70%, single pass processing rate shall not exceed 30%, specifications

[0070] 7) One-pass stretching: The single-pass elongation coefficient is 1.2 to 1.6, specifications

[0071] 8) Primary annealing: annealing temperature is 650-900°C, annealing time is 0.1-2h, and rapid cooling rate is greater than 30°C / s;

[0072] 9) Secondary stretching: single pass elongation coefficient is 0.8~1.5, specification

[0073] 10) Secondary annealing: annealing temperature is 400-650°C, annealing time is 0.5-8h;

[0074] 11) Cleaning: Use ultrasonic cleaning.

[0075] The key process parameter controls of the embodiments of the present invention and the comparative examples are shown in Table 2.

[0076] Comparative Example 1 is C12200.

[0077] The difference between Comparative Example 2 and Example 1 is that the copper alloy tube is prepared by a conventional method on the market. Specifically, compared with Example 1, only one stretching and one annealing are used in the preparation process of this comparative example, and the condition of the one annealing is annealing at 460° C. for 4 hours.

[0078] The prepared embodiment and comparative alloys were subjected to tests on microstructure grain size, compound particle quantity, tensile mechanical properties, pressure resistance, expansion and salt spray corrosion at room temperature. At the same time, microstructure grain size, tensile mechanical properties and pressure resistance were tested in a simulated brazing process environment under high temperature conditions, such as 850°C, 1000°C and 1065°C, after heating for 15s. The specific data are shown in Table 3.

[0079] The average grain size of the metallographic structure is tested in accordance with "GB / T 6394-2017 Method for Determination of Metal Grain Size".

[0080] The room temperature tensile test was carried out on an electronic universal mechanical properties testing machine in accordance with GB / T 228.1-2010 Metallic Materials Tensile Test Part 1: Room Temperature Test Method, with a tensile speed of 5 mm / min.

[0081] The pressure test is carried out in accordance with "GB / T 241-2007 Metal Pipe. Hydraulic Test Method".

[0082] The bending test is carried out in accordance with GB / T 244-2008 Metal Tubes. Bending Test Method. Under the condition that the bending core diameter is 1.5 times the outer diameter of the copper tube, the inner and outer surfaces of the tube are smooth without wrinkles or cracks when bent 180°.

[0083] The salt spray corrosion test was conducted in accordance with GB / T 10125-1997 "Artificial atmosphere corrosion test-Salt spray test". A test tube of 50 mm in length was cut from the tube, degreased and dried, and then placed in a salt spray test chamber with 5% NaCl + 1% CH3COOH. Each different sample tube was taken out for observation and testing every three days, with a maximum time of 42 days. After sampling, the corrosion depth and perforation of the sample tube section were observed. If the maximum corrosion depth of the sample is greater than the wall thickness of the sample tube, it is judged as perforation; if the maximum corrosion depth of the sample is less than the wall thickness of the sample tube, the maximum corrosion depth in the section is recorded. Result statistics: The average maximum corrosion depth of the sample tube is the sum of the maximum corrosion depths of all test sample tubes divided by the number of all test sample tubes, and the perforation rate is the number of perforated samples divided by the number of all test sample tubes.

[0084] The expansion test is carried out in accordance with GB / T 17791-1999 "Seamless Copper Tubes for Air Conditioning and Refrigeration". When the expansion rate (cone punching 60°) of the copper alloy tube is 40% or the distance between the two walls after flattening is equal to the wall thickness, the copper alloy tube sample does not produce visible cracks and fissures, indicating that the copper alloy tube has excellent process performance.

[0085] The bell mouth sealing test uses a helium detector to verify the leakage of the copper tube bell mouth and the pipe joint after tightening (equipped with a stop valve and copper nut). After tightening the torque (24-28N), an electronic leak detector is used for detection. No leakage means good sealing. The number of test samples is 10, and the leakage ratio is calculated. Evaluation method: 1. Test the leakage ratio under normal 24N sealing torque and maximum 28N sealing torque conditions; 2. After tightening at the maximum sealing torque, remove it, and test the leakage ratio after 3 rounds.

[0086] The microstructure properties of the alloys of the embodiments of the present invention and the comparative examples are shown in Table 3. The mechanical properties and processing application properties of the alloys of the embodiments and the comparative examples are shown in Table 4 and Table 5, respectively.

[0087] Table 1 Alloy composition of the embodiments of the present invention and the comparative examples

[0088]

[0089] Table 2 Key process parameter control of the embodiments of the present invention and the comparative examples

[0090]

[0091] Table 3 Microstructure properties of copper alloy tubes of the embodiments of the present invention and comparative examples

[0092]

[0093] Table 4 Mechanical properties of copper alloy tubes of the embodiments of the present invention and comparative examples

[0094]

[0095] Table 5 Processing and application performance of copper alloy tubes of the embodiments of the present invention and comparative examples

[0096]

Claims

1. A copper alloy tube, characterized in that: The invention comprises the following components in percentage by mass: Sn: 0.01-0.80%, P: 0.005-0.05%, Zr: 0.01-0.10%, B: 0.001-0.01%, Mn: 0.001-0.01%, and the balance is Cu and unavoidable impurities; wherein the copper alloy tube contains MnZr and BMn compound particles, and the number of MnZr compound particles on the cross section of the copper alloy tube is 0.005-0.15 / μm 2 The number of BMn compound particles is 0.005 to 0.2 per μm. 2 .

2. The copper alloy tube according to claim 1, characterized in that In the copper alloy tube, the mass ratio of Zr to Mn satisfies: 0.1≤Mn / Zr≤1; the mass ratio of B to Mn satisfies: 0.1≤Mn / B≤8.

3. The copper alloy tube according to claim 1, characterized in that The copper alloy tube has an average grain diameter of 15 μm or less, and a standard deviation of the average grain diameter of 1.5 μm or less.

4. The copper alloy tube according to any one of claims 1 to 3, characterized in that: The copper alloy tube comprises Fe and Si, and the total mass percentage of Fe and Si is less than 0.0030%; And / or; the copper alloy tube includes 0.001-0.01% by mass of X, wherein X is selected from at least one of Mg, Al, Cr, Ni or rare earth elements.

5. The copper alloy tube according to claim 1, characterized in that The yield strength YS of the copper alloy tube in the circumferential direction LD Yield strength YS in the longitudinal direction TD The ratio satisfies: YS LD / YS TD ≥0.

95.

6. The copper alloy tube according to claim 1, characterized in that After the copper alloy tube is heated at 800°C for 15 seconds, the average grain diameter of the microstructure is less than 20 μm, and the bursting pressure is more than 30 MPa; And / or; After the copper alloy tube is heated at 1000°C for 15s, the average grain diameter of the structure is less than 25μm, and the bursting pressure is more than 29MPa; And / or; After the copper alloy tube is heated at 1065°C for 15s, the average grain diameter of the structure is less than 30μm and the bursting pressure is more than 28MPa.

7. The method for preparing a copper alloy tube according to any one of claims 1 to 6, characterized in that: The following steps are involved: Melting → casting → homogenization annealing → extrusion → rolling → primary stretching → primary annealing → secondary stretching → secondary annealing; Wherein, the primary annealing temperature is 650-900°C, the annealing time is 0.1-2h, and the cooling rate after the primary annealing is greater than 30°C / s; The elongation coefficient of the secondary stretching is 0.8 to 1.

5.

8. The preparation method according to claim 7, characterized in that: The secondary stretching passes are 5 to 8 passes, the elongation coefficients of the first two passes are 1.2 to 1.5, and the elongation coefficients of the last three passes are 0.8 to 1.

3.

9. The preparation method according to claim 7 or 8, characterized in that: The secondary annealing temperature is 400-650° C., and the annealing time is 0.5-8 hours.

10. Use of the copper alloy tube according to any one of claims 1 to 6 in preparing heat transfer tubes of air conditioner heat exchangers, connecting pipes for indoor and outdoor units of air conditioners, pipes inside the unit or pipe assemblies.

Citation Information

Patent Citations

  • Copper alloy tube for heat exchanger excellent in fracture strength

    CN101469961A

  • Copper alloy tube for heat exchangers

    CN101430175A

  • Novel copper alloy and copper alloy pipe

    CN102071335A

  • Copper alloy tube

    JP2011225989A

  • Copper alloy tube

    JP2013076123A

Cited By

  • High-strength and high-corrosion-resistance copper alloy pipe as well as preparation method and application thereof

    CN121915290A

  • Micro-alloyed copper alloy pipe and preparation process thereof

    CN122128574A

  • Copper alloy material resistant to ant nest corrosion as well as preparation method and application of copper alloy material

    CN122484547A

  • Batch production method for large-specification high-precision copper alloy pipes

    CN122583420A

  • Large-size high-precision copper alloy pipe batch production method

    CN122583420B